Pengaruh Kecerdasan Emosional dan Motivasi Belajar Siswa terhadap Hasil Belajar Biologi Siswa Kelas X SMAN 9 Gowa - Nurhidaya Nurhidaya; Hilmi Hambali; Nurul Fadhila (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This type of research is survey research. The purpose of this study is to (1) determine the effect of emotional intelligence on the biology learning outcomes of class X students of SMAN 9 Gowa, (2) determine the effect of learning motivation on the biology learning outcomes of class X students of SMAN 9 Gowa, (3) determine the effect of emotional intelligence and learning motivation together on the biology learning outcomes of class X students of SMAN 9 Gowa. The population in this study were all class X students of SMAN 9 Gowa and the selected sample was 153 students. The data collection technique in this study was a questionnaire and documentation. The collected data were then analyzed using descriptive statistical analysis and inferential statistics. The results of the study showed that there was a positive and significant effect between emotional intelligence and learning outcomes. This was proven in the t-test hypothesis testing obtained a value of 4.935 with a significance level of 0.000 <0.05. There was a positive and significant effect between learning motivation and learning outcomes. This was proven in the t-test hypothesis testing obtained a value of 6.965 with a significance level of 0.000 <0.05. So it can be concluded that emotional intelligence and learning motivation play an important role in the learning process, especially in student learning outcomes.